Hit identification against peptidyl-prolyl isomerase of Theileria annulata by combined virtual high-throughput screening and molecular dynamics simulation approach. (December 2020) - Spahi, Sezen; Mutlu, Ozal; Sariyer, Emrah; Kocer, Sinem; Ugurel, Erennur; Turgut-Balik, Dilek
Graphical abstract: Highlights: Theileria annulata has been developing drug resistance against buparvaquone. Ta PIN1 (peptidyl prolyl isomerase) contains a mutation causes the resistance. Ta PIN1 manipulates host cell oncogenic signaling pathway and could be a drug target. Ta PIN1 inhibitors were investigated using a library of naphthoquinone derivatives. Potential inhibitors were identified using docking and simulation analyses. Abstract: Theileria annulata secretes peptidyl prolyl isomerase enzyme ( Ta PIN1) to manipulate the host cell oncogenic signaling pathway by disrupting the tumor suppressor F-box and WD repeat domain-containing 7 (FBW7) protein level leading to an increased level of c-Jun proto-oncogene. Buparvaquone is a hydroxynaphthoquinone anti-theilerial drug and has been used to treat theileriosis. However, Ta PIN1 contains the A53 P mutation that causes drug resistance. In this study, potential Ta PIN1 inhibitors were investigated using a library of naphthoquinone derivatives. Comparative models of mutant (m) and wild type (wt) Ta PIN1 were predicted and energy minimization was followed by structure validation. A naphthoquinone (hydroxynaphthalene-1, 2-dione, hydroxynaphthalene-1, 4-dione) and hydroxynaphthalene-2, 3-dione library was screened by Schrödinger Glide HTVS, SP and XP docking methodologies and the docked compounds were ranked by the Glide XP scoring function. The two highest ranked docked compounds Compound 1 (4-hydroxy-3-[3, 4, 5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxynaphthalene-1, 2-dione) and Compound 2 (6-acetyl-1, 4, 5, 7, 8-pentahydroxynaphthalene-2, 3-dione) were used for further molecular dynamics (MD) simulation studies. The MD results showed that ligand Compound 1 was located in the active site of both m Ta PIN1 and wt Ta PIN1 and could be proposed as a potential inhibitor by acting as a substrate antagonist. However, ligand Compound 2 was displaced away from the binding pocket of wt Ta PIN1 but was located near the active site binding pocket of m Ta PIN1 suggesting that could be selectively evaluated as a potential inhibitor against the m Ta PIN1. Compound 1 and Compound 2 ligands are potential inhibitors but Compound 2 is suggested as a better inhibitor for m Ta PIN1. These ligands could also further evaluated as potential inhibitors against human peptidyl prolyl isomerase which causes cancer in humans by using the same mechanism as Ta PIN1.